2022
DOI: 10.1038/s41598-022-13907-6
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of micro-CT-based whole tissue imaging (WTI) on endoscopic submucosal dissection (ESD) specimens

Abstract: Endoscopic submucosal dissection can remove large superficial gastrointestinal lesions in en bloc. A detailed pathological evaluation of the resected specimen is required to assess the risk of recurrence after treatment. However, the current method of sectioning specimens to a thickness of a few millimeters does not provide information between the sections that are lost during the preparation. In this study, we have produced three-dimensional images of the entire dissected lesion for nine samples by using micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Unfortunately, this method does not allow one to avoid the disadvantages of classical histological examination in the form of unavoidable damage to the sample during the section [ 118 ]. Recent studies have shown the efficacy of histological evaluation in breast, lung, colon, gastric, and thyroid cancer using whole-block imaging (WBI) via micro-CT [ 119 , 120 , 121 , 122 , 123 ]. The role of whole-tissue imaging can be increased due to the necessity for accurate evaluation of margins of surgical resection, initial treatment response, and response to neoadjuvant chemotherapy, and would be considered as a helping hand for pathologists.…”
Section: Untrodden Path: Vasculature Access In Sarcomasmentioning
confidence: 99%
“…Unfortunately, this method does not allow one to avoid the disadvantages of classical histological examination in the form of unavoidable damage to the sample during the section [ 118 ]. Recent studies have shown the efficacy of histological evaluation in breast, lung, colon, gastric, and thyroid cancer using whole-block imaging (WBI) via micro-CT [ 119 , 120 , 121 , 122 , 123 ]. The role of whole-tissue imaging can be increased due to the necessity for accurate evaluation of margins of surgical resection, initial treatment response, and response to neoadjuvant chemotherapy, and would be considered as a helping hand for pathologists.…”
Section: Untrodden Path: Vasculature Access In Sarcomasmentioning
confidence: 99%